Development of a Laboratory Airbag Model to Cushion the effect of Vehicle Tyre Burst While in Motion - Hassan, A. B.; Musa, A.; Babawuya, A.; Yahuza, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The incessant rate of traffic accident as a result of tyre burst on our roads from the motor vehicle necessitated the development of this airbag to cushion the effect of tyre burst. The development of this laboratory airbag model is such that the airbag is incorporated into the rim (i.e. on the rim, inside the tyre). This allows the vehicle balance for some time until the driver is able to maneuver and park the vehicle safely. The frame of the airbag model was made of 0.5 mm ply wood cut into six (6) pieces and to form the box. A hole was drilled at the front to give space for motor to be used as a prime mover. The shaft produced from a 30 mm diameter mild steel rod was machined on a lathe machine to 25 mm diameter and cut to length of 10 mm. The calculated resultant stress upon impact was 83.96 MPa. The contact area and airbag thickness was 0.258 m2 and 2.8 mm, respectively. A mini inflator was selected and actuated with the aid of an infrared sensor; it took less than six (6) seconds to actuate the shape airbag. The laboratory model was powered by a DC source and tyre burst signals were transmitted wirelessly through a control system.